(σ, τ)-Derivations of group rings. Issue 9 (2nd September 2019) - Chaudhuri, Dishari
Abstract: We study ( σ, τ ) -derivations of a group ring RG of a finite group G over an integral domain R with 1. As an application we extend a well known result on derivation of an integral group ring Z G to ( σ, τ ) -derivation on it for a finite group G with some conditions on σ and τ . In the process of the extension, a generalization of an application of Skolem-Noether Theorem to derivation on a finite dimensional central simple algebra has also been given for the ( σ, τ ) -derivation case.